Punicalagin Reverses Methotrexate-Induced Nephrotoxicity by Attenuating Oxidative Stress, Inflammation and Apoptosis: Pharmaceutical Sciences-Pharmacy for better health - Aladaileh, Saleem H.; Swailmi, Farhan K. Al-; Abukhalil, Mohammad H.; Shalayel, Mohammed H. (International Journal of Life Science and Pharma Research, 2021)
Methotrexate (MTX) is a trusted anticancer agent; however, its multi-organ toxicity limits its clinical application, including nephrotoxicity. Punicalagin (PUN) is an ellagitannin found in the fruit peel of Punicagranatum with anti-inflammatory and antioxidant properties. The present study aimed to investigate the renoprotective effects of PUN in a well-established rat model of MTX-induced nephrotoxicity. Rats were divided randomly into four groups (six animals per group) as follows: the first group (control) was a normal control group. The second group (PUN) received PUN (30 mg kg- 1 day- 1) daily through oral gavage for 10 consecutive days. The third group (MTX) a single i.p. injection of MTX (20 mg/kg) on day 7. The fourth group (PUN + MTX) received PUN (30 mg kg- 1 day- 1) via oral gavage for 10 consecutive days and a single i.p. injection of MTX (20 mg/kg) on day 7. MTX-induced nephrotoxicity was associated with increased creatinine and urea in the serum. MTX also resulted in increased oxidative stress as evidenced by elevated malondialdehyde and protein carbonyl levels along with decreased glutathione content and superoxide dismutase and catalase activities in the kidney. Moreover, renal tissues were characterized by increased proinflammatory cytokines, cytochrome c and caspases-3, indicating increased inflammation and apoptosis in the kidney. PUN pretreatment prevented kidney injury, oxidative stress, inflammation and apoptosis, and enhanced antioxidant defenses in the kidney. Collectively, these findings indicate that PUN may represent a novel renoprotective strategy against MTX-induced oxidative stress, inflammation and apoptosis in the kidney, which deserves further exploration in future studies.